2018
DOI: 10.1111/gtc.12629
|View full text |Cite
|
Sign up to set email alerts
|

Sfh1, an essential component of the RSC chromatin remodeling complex, maintains genome integrity in fission yeast

Abstract: Abp1 is a fission yeast CENP-B homologue that contributes to centromere function, silencing at pericentromeric heterochromatin and silencing of retrotransposons. We identified the sfh1 gene, encoding a core subunit of the fission yeast chromatin remodeling complex RSC as an Abp1-interacting protein. Because sfh1 is essential for growth, we isolated temperature-sensitive sfh1 mutants. These mutants showed defects in centromere functions, reflected by sensitivity to an inhibitor of spindle formation and minichro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Although the chromatin receptors differ, a common requirement for accessible nucleosome-free DNA in open chromatin might unite the SMC complexes. Condensin also loads at open promoter regions in fission yeast, C. elegans , and human cells, whereas the fission yeast RSC complex has been implicated in the loading of both cohesin and condensin onto chromosomes (Kotomura et al., 2018, Kranz et al., 2013, Sutani et al., 2015, Toselli-Mollereau et al., 2016). Given that DNA has to pass through protein-protein interfaces to enter an SMC ring (Murayama and Uhlmann, 2015), it is plausible that nucleosomes pose a steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chromatin receptors differ, a common requirement for accessible nucleosome-free DNA in open chromatin might unite the SMC complexes. Condensin also loads at open promoter regions in fission yeast, C. elegans , and human cells, whereas the fission yeast RSC complex has been implicated in the loading of both cohesin and condensin onto chromosomes (Kotomura et al., 2018, Kranz et al., 2013, Sutani et al., 2015, Toselli-Mollereau et al., 2016). Given that DNA has to pass through protein-protein interfaces to enter an SMC ring (Murayama and Uhlmann, 2015), it is plausible that nucleosomes pose a steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Many cellular factors regulate retrotransposon RNA levels in S. pombe in addition to the RNAi and exosome pathways previously discussed. Tf2 transcription is repressed by many proteins, including the chromodomain protein Swi6, the HIRA histone chaperone complex, the histone methyltransferases Clr4 and Set1, the RSC chromatin remodeling complex subunit Sfh1, the histone deacetylases Clr3, Clr6, and Hst4, as well as the Nts1 protein present in one specific Clr6 complex [115,119,120,[207][208][209][210][211][212][213]. Furthermore, the CENP-B homologs Cbp1/Abp1, Cbh1, and Cbh2 that are involved in establishing centromeric heterochromatin also negatively regulate Tf2 transcription [208].…”
Section: Schizosaccharomyces Pombementioning
confidence: 99%
“…In addition, a low concentration of TBZ enhanced the chromosome segregation defects of the temperature-sensitive sfh1-13 mutant ( Supplementary Figure S1A ). These results suggest a role for RSC in accurate chromosome segregation, although the level of CENP-A Cnp1 at the central domain, and the amount of H3K9me at the pericentromeric domain, do not change in sfh1-13 cells ( 12 ). Previous work has shown that mutations of the histone chaperon FACT and the 19S proteasome can cause inappropriate deposition of CENP-A Cnp1 at non-centromeric regions when CENP-A Cnp1 is overexpressed, leading to slow growth ( 22 , 23 ).…”
Section: Resultsmentioning
confidence: 79%
“…RSC localizes at both the kinetochore domain and pericentromeric heterochromatin. Temperature-sensitive mutants of sfh1 or snf21 , core subunits of RSC, are sensitive to the microtubule-destabilizing drug thiabendazole (TBZ) and exhibit an elevated rate of minichromosome loss ( 11 , 12 ). Mutants that disrupt chromosome segregation are often hypersensitive to TBZ ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation